Nobiletin attenuates acetaminophen-induced hepatorenal toxicity in rats - Guvenc, Mehmet; Cellat, Mustafa; Gokcek, Ishak; Ozkan, Huseyin; Arkali, Gozde; Yakan, Akin; Aksakal, Mesut (Wiley, 2020)
The study aimed to examine the effects of nobiletin on the toxicity model induced with acetaminophen (APAP). For this purpose, 24 adult male rats were equally divided into four groups. The groups were the control group (group 1); dimethyl sulfoxide only, the APAP group (group 2) received a single dose of APAP 1000 mg/kg on the 10th day of experiment; the Nobiletin group (group 3), nobiletin (10 mg/kg) for 10 days; and the APAP + Nobiletin group (group 4), nobiletin (10 mg/kg) for 10 days with a single dose of APAP (1000 mg/kg) administered on the 10th day and the experiment ended after 48 hours. At the end of the study, a significant increase in malondialdehyde, interleukin-1 beta (IL-1 beta), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-alpha) levels and a significant decrease in glutathione levels, glutathione peroxidase activities and nuclear factor erythroid-derived 2-like 2 (Nrf-2) and heme oxygenase-1 (HO-1) expressions were observed with APAP application in liver and kidney tissues. Serum aspartate transaminase (AST), alanine transaminase (ALT), urea, and creatinine levels were also significantly increased in the APAP group. However, nobiletin treatment in group 4 reversed oxidative stress and inflammatory and histopathological signs caused by APAP. It is concluded that nobiletin may be a beneficial substance that confers hepatorenal protection to APAP-induced toxicity via antioxidant and anti-inflammatory mechanisms.
Keywords: acetaminophen; nobiletin; Nrf-2; HO-1; oxidative stress